Meat intake and bladder cancer in a prospective study: A role for heterocyclic aromatic amines? - Lumbreras, B; Garte, S; Overvad, K; Tjonneland, A; Clavel-Chapelon, F; Linseisen, J; Boeing, H; Trichopoulou, A; Palli, D; Peluso, M; Krogh, V; Tumino, R; et al. (2008)
Background: The suspect carcinogens, heterocyclic amines (HAAs), found in well-done meat require host-mediated metabolic activation before inducing DNA mutations. The role of SULT1A1 and of NAT2 on the activation of HAAs suggests that NAT2 rapid acetylator genotype and SULT1A1 allele variants can have an effect on HAA carcinogenicity. Methods: Data were collected as part of a case-control study nested within the EPIC cohort, the Gen Air investigation. EPIC is a prospective study designed to investigate the relationship between nutrition and cancer. Information was collected through a non-dietary questionnaire on lifestyle variables and through a dietary questionnaire. The subjects were restricted to non-smokers. We calculated the matched odds ratio for bladder cancer risk using logistic regression, controlling for potential confounders. Results: There were 227 bladder cases and 612 controls matched 1:3. Meat intake and NAT2 genotype were not independently associated with bladder cancer risk. A significant relationship was observed between bladder cancer risk and consumption of meat only among subjects with the rapid NAT2 genotype (odds ratios [OR] 2.9, 95% CI 1.0-7.9 for the 2nd quartile of meat intake; 3.6, 95% CI 1.3-9.7 for the 3rd quartile; and 3.5, 95% CI 1.2-9.7 for the 4th quartile), and was not present among subjects with the slow genotype. An interaction between NAT2 and meat intake was found in logistic regression (P = 0.034). No association was observed for SULT1A*1/2 genotype (1.0; 95% CI 0.7-1.5) and for SULT1A1*2/2 genotype (0.9; 95% CI 0.5-1.7). Conclusions: These results are suggestive of a role of meat intake and NAT2 on bladder cancer risk. They support the hypothesis that among subjects with the rapid NAT2 acetylation genotype higher levels of HAAs exposure are a bladder cancer risk factor. We did not observe an effect of SULT1A1 allele variants on this cancer. The present study adds new information on the possible long-term adverse effects of diets with high meat intake. © 2008 Springer Science+Business Media B.V.